Enhancing bacterial survival through phenotypic heterogeneity - Reyes Ruiz, Leila M.; Williams, Caitlin L.; Tamayo, Rita (PLoS pathogens, 2020)
Variations in the number of nucleotides within an SSR in a coding sequence may cause a frameshift mutation that creates a premature stop codon and a truncated product (OFF) or, conversely, may restore the reading frame and production of the gene product (ON). [...]phase variation can be achieved by shuffling alleles of the same gene between an expressed locus and a distal, silent locus. Consistent with this result, phase-locked OFF mutants lacking fimbriae are attenuated in disease models of urinary tract infection [12, 13]. Some DNA methyltransferases, enzymes that methylate specific nucleotide motifs, are subject to phase variation, resulting in a population of bacteria with different methylation patterns. Because methylation can influence gene expression, methyltransferase phase variation can influence the transcription of multiple genes simultaneously.